Factors associated with the transmission of soil-transmitted helminthiasis among schoolchildren - Isra Firmansyah; Sri Alemina Ginting; Munar Lubis; Iskandar Z Lubis; Syahril Pasaribu; Chairuddin P Lubis (Indonesian Pediatric Society, 2004)
Background Soil-transmitted helminthiasis (STH) is an importantpublic health problem in Indonesia.Objective To find out factors influencing the transmission of STHin two different communities in North Sumatera, Indonesia.Methods A cross sectional study was done on 96 primary schoolchildren in Suka village (located on a mountain area) and 96 pri-mary school children in Pantai Cermin village (a coastal area). Sub-jects were recruited by simple random sampling. Kato Katz andcentrifuge floatation methods were used for stool and soil exami-nations, respectively. Data were collected by interviewing parentsof children using a questionnaire and were analyzed using chi–square test by SPSS program version 11.0.Results There was no difference in the prevalence of STH in bothvillages (p>0.05). Parents’ knowledge and economic status hadsignificant relationships with the prevalence of STH in Suka vil-lage (p<0.05), but not in Pantai Cermin (p>0.05). In both villages,parents’ education did not have a significant relation with STH,while there were significant relations between STH and hygiene,environment, or soil contamination by worm eggs (p<0.05).Conclusion There were significant relationships between hygiene,environment, or soil contamination and the prevalence of STH inthe two villages.